"We're Not Ready, But I Don't Think You're Ever Ready." Clinician Perspectives on Implementation of Crisis Standards of Care. Issue 3 (2nd July 2020) - Chuang, Elizabeth; Cuartas, Pablo A.; Powell, Tia; Gong, Michelle Ng
Abstract: Background: The COVID-19 pandemic has highlighted health care systems' vulnerabilities. Hospitals face increasing risk of periods of scarcity of life-sustaining resources such as ventilators for mechanical respiratory support, as has been the case in Italy as of March, 2020. The National Academy of Medicine has provided guidance on crisis standards of care, which call for the reallocation of scarce medical resources to those who will benefit most during extreme situations. Given that this will require a departure from the usual fiduciary duty of the bedside clinician, we determined and mapped potential barriers to the implementation of the guidelines from stakeholders using an implementation science framework. Methods: A protocol was created to operationalize national and state guidelines for triaging ventilators during crisis conditions. Focus groups and key informant interviews were conducted from July-September 2018 with clinicians at three acute care hospitals of an urban academic medical center. Respiratory therapists, intensivists, nursing leadership and the palliative care interdisciplinary team participated in focus groups. Key informant interviews were conducted with emergency management, respiratory therapy and emergency medicine. Subjects were presented the protocol and their reflections were elicited using a semi-structured interview guide. Data from transcripts and notes were categorized using a coding strategy based on the Theoretical Domains Framework. Results: Participants anticipated that implementing this protocol would challenge their roles and identities as clinicians including both their fiduciary duty to the patient and their decision-making autonomy. Despite this, many participants acknowledged the need for such a protocol to standardize care and minimize bias as well as to mitigate potential consequences for individual clinicians. Participants identified the question of considering patient quality of life in triage decisions as an important and unresolved ethical issue in disaster triage. Conclusion: Clinicians' discomfort with shifting roles and obligations could pose implementation barriers for crisis standards of care.